The early impact of the COVID-19 pandemic on mathematical competencies on entry into a UK university. (8th October 2021) - Hodds, Mark
Abstract: Students from England and Wales had their A-level results in 2020 decided by a 'triple lock' system as traditional examinations were cancelled due to the pandemic. Therefore, there was a fear that students were either being unfairly judged ( Arden University 2020 ) or would enter university with a reduced understanding of concepts leading to an increase in drop-out rates ( Staton, 2020 ). To measure mathematical ability, diagnostic testing is used at universities. This is now a well-established practice that supports students and their lecturers in discovering areas of mathematical strength and weakness upon entry to a course ( Lawson, 2003 ; Hodds, Shao, and Lawson, 2020 ). This article compares the entry competencies of students arriving at one UK university in October 2020 with those who entered in previous years, using the same diagnostic test taken by all students as the method for comparison. Students who received their A levels in the year of entry are also compared to those who entered with A levels from years prior, allowing for a fair comparison of students in 2020 in particular. Furthermore, the abilities of students at different A-level grades are also compared. The results showed that students in 2020 appear not to be disadvantaged by the issues caused by the pandemic. On the contrary, many students outperformed colleagues who had summative assessment prior to 2020.